Factors influencing consumers' purchase intention and behaviour on live shopping platforms in the post-epidemic era - SUI, Muqi (2022)
Using the TAM, TPB model, and two separate factors, discount, and epidemic, this paper examines the factors influencing purchase intentions of users of live shopping platforms in the post-epidemic era and tests the hypotheses by collecting data through a questionnaire. It was found that there were two perceptual factors in the TAM that had significant indirect effects on purchase intention, with attitude as an important mediator corresponding to two types of motivations for people to watch live streaming, hedonic and utilitarian, respectively (Cai et al., 2018). The significant effects of attitudes and subjective norms on purchase intention in the TPB model reflect the real-time nature of live shopping, i.e. the ability to communicate with sellers in real-time and establish emotional connections, while the significant effect of subjective norms validates that in a collective society, people's willingness to purchase goods is influenced internally by family, friends, etc., and externally by authoritative experts, media, etc. Furthermore, the results of this study do not show a significant effect of discounts on users, which could be related to sensible consumer behavior.